2018
DOI: 10.1038/s41598-018-33612-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a two-SNP PLA2R1 Haplotype and HLA-DRB1 Alleles as Primary Risk Associations in Idiopathic Membranous Nephropathy

Abstract: The associations of single nucleotide polymorphisms (SNPs) in PLA2R1 and HLA-DQA1, as well as HLA-DRB1*15:01-DQB1*06:02 haplotype with idiopathic membranous nephropathy (IMN) is well known. However, the primary associations of these loci still need to be determined. We used Japanese-specific SNP genotyping array and imputation using 2,048 sequenced Japanese samples to fine-map PLA2R1 region in 98 patients and 413 controls. The most significant SNPs were replicated in a separate sample set of 130 patients and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…among untreated patients, approximately one third undergo spontaneous remission, one-third progress to end-stage renal disease over 10 years and the remainder develop non-progressive cKd. in short, approximately two-thirds of cases progress to cKd (12)(13)(14)(15). Thus far, no curative therapies have been achieved for cKd or iMn (16,17), which may be attributed to unclear mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…among untreated patients, approximately one third undergo spontaneous remission, one-third progress to end-stage renal disease over 10 years and the remainder develop non-progressive cKd. in short, approximately two-thirds of cases progress to cKd (12)(13)(14)(15). Thus far, no curative therapies have been achieved for cKd or iMn (16,17), which may be attributed to unclear mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The authors 10 have reported the SNPs rs3749119, rs3749117, rs35771982, rs3828323, and rs4664308 as crucial for causing Nephropathy. Further 11 , have identified the two SNPs rs3749117 and rs35771982 that are causing protein level changes to the protein hence effecting its function. The experimental analysis carried out by 12 showed that rs6757188 and rs3577198 are highly associated with idiopathic membranous nephropathy (IMN) and that's maybe the underlying cause of IMN.…”
mentioning
confidence: 99%
“…In Caucasian population, genome-wide association studies have confirmed the susceptibility of PLA2R and HLA-DQA1 gene with PMN [ 13 ]. Multiple loci in PLA2R and HLA-DQA1 were closely related to PMN in various ethnicities, but the results of different regions and ethnic groups were not entirely consistent [ 8 , 13 18 ]. To verify the previous findings in Western China, in our previous study we selected eight SNPs reported in the literatures and found that two SNPs (rs2715918, rs4665143) within PLA2R , 1 SNP in HLA-DQA1 (rs2187668) were associated with primary membranous nephropathy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%